A literature review on depression and its risk factors among people suffering from chronic obstructive pulmonary disease in Asian sub-continent - Sharma, Amrit (International Journal Of Community Medicine And Public Health, 2020)
Chronic obstructive pulmonary disease (COPD) is defined as persistent airflow limitation that is usually progressive and associated with an enhanced chronic inflammatory response in the airways and the lung to noxious particles or gases. It has been suggested that emotional disturbances such as depression and anxiety are common among patients with COPD. This review aims to highlight the presence of depression and associated risk factors among patients suffering from COPD in Asia. Fifty-eight observational studies were retrieved through data sources like PubMed, Medical subject heading (MeSH) search and Google scholar. After thorough screening total thirteen studies were identified and included in this review. Based on the results of these studies, the south and west Asian countries had higher proportion of depression. However, risk factor results were mixed which includes severity of obstruction/global initiative for obstructive lung disease (GOLD) criteria, Stage 2 COPD, teetotallers, smoking, alcohol consumption, body mass index, airflow obstruction, dyspnoea, and exercise (BODE) index, urban residence, female gender, education level, dyspnoea, low income, poor Quality of life (QOL) scores, age, poor self-reported health, basic activity of daily living (BADL) disability. Further superior research studies with larger sample size are required on Asian population. All in all, it is recommended that early diagnosis and treatment of depression should be included as a part of management in COPD as it can help to minimize the risk of morbidity and mortality in the patients.